ANALISIS PENGARUH MOTIVASI INTERNAL TERHADAP FASE PRA-BENCANA DI DUSUN WONOSARI DAN SUKOSARI, DESA PANDANSARI, KEC. PONCOKUSUMO KAB. MALANG - Debora, Oda; Wibowo, Wibowo (Journal Nursing Care and Biomolecular, 2018)
Introduction: Community resiliency is one of important factor in order to encounter disaster and accelerate recovery phase after a disaster occur. To enhance this resilience, various efforts can be done during pre-disaster phase. However, without intense internal motivation, this efforts were useless. The aim of this research was to find out the internal motivation which has a dominant influence on the pre-disaster phase. Method: This research was a non-experimental with cross-sectional design. Data was collected in one time for each respondent using a questionnaire. Partial Least Square test were done to found out the most influential components in internal motivation and pre-disaster phase and the relational strength between those two variables Result and Analysis: Internal motivation affected pre-disaster phase, it was shown by t score 2,508. Variables which contributed predominantly to internal motivation was knowledge which was indicated by a t value of 2.074. Whereas the pre-disaster phase which contributed predominantly was Expedient hazard Mitigation which was indicated by t value of 21,346. Discussion: It can be concluded that the provision of sustainable knowledge to the population can improve the population ability to recognize vulnerabilities in their location and create a better mitigation system. Nurses can improve the community ability in mitigation through the continuous delivery of knowledge about disasters and first aid in a sustainable emergency. Mitigation was not confined only for environment, it also concluded community resources mitigation as well. Economic mitigation was the prior consideration thought by the community, especially for those who had middle-low income.